已知M-2N=0.求[1+(N/M)-M/(M-N)]/[1-(N/M)-M/(M+N)]
3个回答
简化的出(M+N)/(M-N)
由M-2N=0 得出M=2N
带入简化后式子
结果=3
相关问题
已知2m-5n=0,求值:(1+n/m-m/m-n)÷(1-n/m-m/m+n)
已知2m-5n=0,求(1+n/m-m/m-n)/(1-n/m-m/m+n)的值
已知2m-5n=0,求(1+(n/m)-(n/m-n))除以(1-(n/m)-(m/m+n))的值
已知|m-1|+|m+2n|=0 求试|m-n|+|m+n|
(1)已知|2m-5|+(2m-5n+20)²=0,求(m-n)²-(2m+n)(n-m)
已知m,n满足m^2--3m=1,n^2--3n=1 求n/m+m/n
已知1/m+1/n=1/m+n,则m*m/n*n+n*n/m*m
已知m,n满足(m-2)²+|½n+1|=0.求[(3m-n)²-(2m+n)²
已知2m²-5m-1≒0,1/n²﹢5/n-2≒0.求n/m+m/n的值
已知实数m、n满足m2-4m-1=0,n2-4n-1=0,则[m/n]+[n/m]=______.